Innovation As school life: A Case Analysis of Andalusia Using a "Concerns-Based Adoption Model" - Gijón Puerta, José (Education Policy Analysis Archives, 2006)
The development of an educational norm (Charter of Students’ Rights and Obligations) in secondary schools in Andalusia is analyzed from the point of view of teachers and educators. To complement the analysis of the documents that regulate secondary schools in the region, a questionnaire with 41 questions was administered to 184 teachers in 24 Andalusian schools. The results, calculated using the CBAM (Concerns-Based Adoption Model), LoU (Level of Use) scale, were then subjected to a descriptive statistical study using measures of central tendency and variability.